2013
DOI: 10.1186/1556-276x-8-416
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-containing nano-sized islands grown on Ge(111)-c(2 × 8) and Ag/Ge(111)-(√3 × √3) surfaces

Abstract: The formation of nano-islands on both a Ge(111)-c(2 × 8) surface and an Ag/Ge(111)-(√3 × √3) surface evaporated with 0.1 ML Ni was investigated by scanning tunneling microscopy (STM). We have noticed that at temperatures lower than 670 K, the reaction between Ni and the individual substrate surfaces proceeds to form different structures: flat-topped islands with a 2√7 × 2√7 or a 3 × 3 reconstruction on the Ni/Ge(111)-c(2 × 8) surface vs. islands with a 7 × 7 reconstruction on the Ni/Ag/Ge(111)-(√3 × √3) surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Most of these investigations were thus carried out by means of spatially averaging characterization techniques and only few methods with nanoscale resolution were applied to study in situ the Ni-Ge interaction [29]. Scanning tunneling microscopy (STM) studies were, to the best of our knowledge, reported insofar for the Ni/Ge(111) system only [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these investigations were thus carried out by means of spatially averaging characterization techniques and only few methods with nanoscale resolution were applied to study in situ the Ni-Ge interaction [29]. Scanning tunneling microscopy (STM) studies were, to the best of our knowledge, reported insofar for the Ni/Ge(111) system only [30,31].…”
Section: Introductionmentioning
confidence: 99%